2015
DOI: 10.1007/s10461-015-1080-4
|View full text |Cite
|
Sign up to set email alerts
|

Health Outcomes of HIV-Infected People with Mental Illness

Abstract: Improving outcomes for people with HIV and mental illness will be critical to meeting the goals of the US National HIV/AIDS Strategy. In a retrospective analysis of the 2008–2010 cycles of the locally representative Philadelphia Medical Monitoring Project, we compared the proportions of HIV-infected adults with and without mental illness: (1) retained in care (≥2 primary HIV visits separated by ≥90 days in a 12-month period); (2) prescribed antiretroviral therapy (ART) at any point in a 12-month period; and (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 37 publications
2
27
2
Order By: Relevance
“…Neither alcohol nor NIDU was statistically associated with retention in care in our primary analysis, as found in another study [ 38 ]. However, when the number of drinks was included in the analysis (instead of any alcohol use), a larger number of drinks increased the chance of not being retained in care.…”
Section: Discussionsupporting
confidence: 67%
“…Neither alcohol nor NIDU was statistically associated with retention in care in our primary analysis, as found in another study [ 38 ]. However, when the number of drinks was included in the analysis (instead of any alcohol use), a larger number of drinks increased the chance of not being retained in care.…”
Section: Discussionsupporting
confidence: 67%
“…Participants who had achieved DVS were less likely to report severe depression compared with those who had achieved SVS. Previous studies have shown poor HIV outcomes among persons with a mental health condition (45,46). Even with the support of the patientcentered interventions, 80% of CJI Black male participants had not achieved DVS which may point to the need for more integrated and/or structural-focused strategies to support medication adherence and DVS among this sample of participants (47,48).…”
Section: Changes In Viral Suppression and Correlates Of Dvsmentioning
confidence: 73%
“…PLWH with a history of injection drug use were reported to be less likely to access ART in several studies 24,25 . Another study in Philadelphia observed that PLWH who had mental illness were less likely to achieve viral suppression than PLWH without mental illness (adjusted OR 0.65, 95 % CI 0.47-0.91) 26 . These findings indicate that more outreach and/or services are needed to help those with mental health and substance use disorders.…”
Section: Discussionmentioning
confidence: 99%